2021
DOI: 10.3389/fpls.2021.765383
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Changes of DNA Methylation During Wild Strawberry (Fragaria nilgerrensis) Tissue Culture

Abstract: Tissue culture is an important tool for asexual propagation and genetic transformation of strawberry plants. In plant tissue culture, variation of DNA methylation is a potential source of phenotypic variation in regenerated plants. However, the genome wide dynamic methylation patterns of strawberry tissue culture remain unclear. In this study, we used whole-genome bisulfite sequencing (WGBS) to study genomic DNA methylation changes of a wild strawberry Fragaria nilgerrensis at six stages: from explants of shoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…Additionally, during the dedifferentiation and redifferentiation stages of the tissue culture process, differentially methylated regions were detected, which were mostly transposable elements. This finding suggests that dedifferentiation and redifferentiation processes were involved in activation or silencing of transposable elements (Cao et al, 2021). Sikdar et al (2022) demonstrated the interaction between cytosine methylation and secondary metabolites in tissue-culture shoots, lingonberry plants, and cutting propagated plants under in vitro and ex vitro conditions.…”
Section: In Vitro Propagation and Epigenetic Variationmentioning
confidence: 90%
See 3 more Smart Citations
“…Additionally, during the dedifferentiation and redifferentiation stages of the tissue culture process, differentially methylated regions were detected, which were mostly transposable elements. This finding suggests that dedifferentiation and redifferentiation processes were involved in activation or silencing of transposable elements (Cao et al, 2021). Sikdar et al (2022) demonstrated the interaction between cytosine methylation and secondary metabolites in tissue-culture shoots, lingonberry plants, and cutting propagated plants under in vitro and ex vitro conditions.…”
Section: In Vitro Propagation and Epigenetic Variationmentioning
confidence: 90%
“…Among these two tissue culture systems, explants from the bioreaction system showed increased levels of methylation variation and polymorphism than explants derived from the semisolid media (Ghosh et al, 2021a). Cao et al (2021) studied genomic DNA methylation using whole genome bisulfite sequencing (WGBS) in wild strawberry (F. nilgerrensis) at various tissue culture stages, starting from use of the shoot tip explants to out planting and acclimation. The authors found that the most obvious methylation changes occurred in the transposable element region of the genome, and the global methylation levels alternately increased and decreased during the tissue culture process.…”
Section: In Vitro Propagation and Epigenetic Variationmentioning
confidence: 99%
See 2 more Smart Citations
“…High quality RNA was extracted from F. nilgerrensis leaves and reversely transcribed into cDNA and used as template for qRT-PCR. Consistent with the qRT-PCR method described in our previous study [90], FnACTIN was selected as an internal reference to normalize the relative expression of each gene. The primer sequences used for qRT-PCR validation are shown in Supplementary Table S7.…”
Section: Qrt-pcr Analysismentioning
confidence: 99%